Budidaya Berlapis Sayuran-Ikan di Kawasan Urban pada Zona Iklim Tropis - Lakitan, Benyamin; A. Muda, Strayker (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Lakitan, B., & Muda, S. A. (2024). Layered cultivation of vegetable-fish in urban areas at the tropical climate zone. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 1–10). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The land area for agricultural cultivation is continuously declining due to conversion for various economic and social interests, so that limited spaces in urban areas also need to be managed for vegetable and fish cultivations. The purpose of this study is to increase the productivity of limited spaces in urban areas through layered cultivation of vegetables and fishes. Shallow concrete fish tanks (45 cm) are used for freshwater fish cultivation (catfish, tilapia, climbing perch) and on the water surface are placed rafts using recycled plastic bottles (1.5 liters) as a float for the cultivation of leafy vegetables with a short harvest cycle (< 3 months). The climbing frame is 2 meters high designed for the cultivation of climbing fruit vegetables (ridged gourd, bitter gourd, cucumber). The results of this study show that the three types of fish used can grow and develop in shallow fish tank where the catfish develop faster, on the other hand, the climbing perch grow much slower. The plant medium in the floating vegetable cultivation system is always moist so it does not need to be watered during its growth cycle. Small-leaved liana plants (bitter gourds) are better to use than broad-leaved ones (ridged gourd, cucumbers) because they reduce the intensity of sunlight that plants receive on the floating raft underneath. Based on results of the research that has been carried out, layered vegetable cultivation can be recommended to be applied by urban communities in utilizing the narrow space available.